New forms of artivism in relation to contemporary societies. Tuty Moreno Campos’s soft artivism - Sousa, Sofia (Frontiers in Sociology, 2025)
With this article, we intend to look at the intersection between the experiences of women artists, particularly in terms of their individual and collective practices, in relation to the creation of art products with an artivist or art-based activism slant. Based on the artistic practice of Tuty Moreno Campos - a migrant artist - we intend to highlight and discuss a new type of art-activist work, in other words, to discuss the emergence of concepts such as soft artivism. To do this, we used a qualitative methodology based on techniques such as semi-structured interviews and content and visual analysis.